Serum calcium and lipid profile in acute ischemic stroke - Sharmin, Nazia; Sultana, Nasima; Mazumder, Pinke; Rahman, Taniza (Bangladesh Journal of Medical Science, 2015)
Background: Worldwide acute ischemic stroke (AIS) is a major public health problem. Therefore, this study was undertaken to see the association of some biochemical risk factors with AIS in Bangladesh. Methodology: This study was conducted in Biochemistry department of Dhaka Medical College, Dhaka from January 2014 to December 2014. In this study, 50 patients of AIS considered as case and 50 age and sex matched healthy individuals taken as control. Blood sample was collected and tested for serum calcium and lipid profile in case and control. All the parameters then compared statistically between two groups. Results: Study showed that serum calcium was significantly lower (p= 0.001) in cases and serum TChol, TAG, LDL-C significantly higher (p= 0.035, 0.001 and 0.019 respectively) and HDL-C significantly lower (0.001) in cases compared to controls. Conclusions: This study concludes that low serum calcium level and altered lipid profile are significantly associated with AIS. Bangladesh Journal of Medical Science Vol.14(3) 2015 p.286-289